ROAD ACCIDENTS IN RUSSIA: ECONOMIC AND STATISTICAL ANALYSIS - N. Cheremisina; T. Cheremisina; Y. Grishko (Вестник Северо-Кавказского федерального университета)
In recent years, the issue of death and disability as a result of road accidents has become very relevant in Russia. As a result of road accidents, millions of Russians are killed and injured, not to mention the economic damage, which amounts to billions of rubles. In order to improve road safety in accordance with presidential decree No. 204 of 7 may 2018 «On national goals and strategic objectives for the development of the Russian Federation for the period up to 2024», the state project «Safe and high-quality roads» has entered into force. In this article, the authors attempt to assess the effectiveness of this project. On the basis of official statistics, an analysis of road accidents in Russia for 2012-2019 was conducted; the dynamics of accidents, injuries, and deaths as a result of road accidents were studied; the reasons are identified and the assessment of changes in the situation for the problem being solved is given. In conclusion, the relevant conclusions are made about possible ways to solve the problem of road accidents in Russia